Assessment of minimal clinically important improvement by using Oral Health Impact Profile-14 in Behçet's disease - (:unkn) unknown (My University, 2009)
Objectives. The aim of this prospective study was to detect minimal clinically important improvement (MCII) of oral health impact profile-14 (OHIP-14) for assessing the effect of treatments for oral ulcers in Behçet's disease (BD). Methods. BD patients with active oral ulcers (F/M:36/22) were selected. Baseline and follow-up data were collected by clinical examinations and questionnaires. Patients rated their global impression of change (PGIC) measured by a transitional question. MCII was defined as the difference in mean change from baseline in OHIP-14 between patients with no response to therapy and patients with next higher level of response. Results. Approximately one third (29.3 %) of the patients expressed an improvement during control examinations. A significant correlation was observed between raw change in OHIP-14 score and change in number of oral ulcers (r=0.69 p=0.017). Inactive patients increased from 44.1 % in baseline to 58.8% in follow-up examination. A trend towards decreased number of oral ulcers was observed in follow-up (0.64±0.93) compared to baseline (1.44±1.92) in the improved group (p=0.096). According to regression analysis, PGIC was a significant predictor of change in raw OHIP-14 score. The threshold levels generated from the ROC analyses in OHIP-14 score best associated with clinically important improvement were -3.5 points (sensitivity: 80%, specificity: 88.6%) and -38.1% (sensitivity: 86.7%, specificity: 97.1%) respectively. Conclusion. Changes in OHIP-14 scores seem to be a sensitive and valuable tool for the determination of MCII during follow-up of Behçet's disease patients for oral disease assessment. © Copyright Clinical and Experimental Rheumatology 2009.
Keywords: Behçet's disease; Improvement; MCII; OHIP-14; Oral ulcer